The effect of circumcision on young adult sexual function. Issue 6 (9th December 2013) - Yang, Ming‐Hsin; Tsao, Chih‐Wei; Wu, Sheng‐Tang; Chuang, Feng‐Ping; Meng, En; Tang, Shou‐Hung; Sun, Guang‐Huan; Yu, Dah‐Shyong; Chang, Sun‐Yran; Cha, Tai‐Lung
Abstract: Whether sexual function is affected by circumcision is a subject of considerable debate among advocate and opponent opinions. We analyzed the sexual function of young men, and the differences between those who were uncircumcised and circumcised, in Taiwan. A total of 506 patients who received circumcision between January 2009 and March 2011 at the urology department in our center were enrolled. Before circumcision, the patients' sexual performances were evaluated using the International Index of Erectile Function‐5 (IIEF‐5), and the Brief Male Sexual Function Inventory (BMSFI) questionnaires. They were evaluated using the questionnaires again, after a postoperative interval of 90 days. Furthermore, intravaginal ejaculation latency times (IELT) of the patients were also measured. The IELT and scores in five main domains of the BMSFI, and IIEF, before and after circumcision, were analyzed. A total of 442 patients were available for follow up. The mean age was 25.14 ± 4.46 years (range = 19–35 years). The differences in the BMSFI scores were statistically significant ( p  < 0.001), especially in increasing sex drive after circumcision ( p  < 0.001). The IIEF‐5 score showed no statistically difference before and after circumcision ( p  = 0.141). However, after the circumcision, the participants had more erection confidence ( p  < 0.001), more difficulty in maintaining erections in completing intercourse ( p  = 0.01), and showed lower IELT scores ( p  = 0.06). The sexual performance, especially with regards to sex drive and mental erection confidence, seemed to have improved among the patients after circumcision. Our findings may help urologists to better counsel young men receiving circumcisions.